From Transcendental Idealism to Transcendental Empiricism - Pachilla, Pablo (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
In the present text, we will inquire into the passage from Immanuel Kant’s transcendental idealism to Gilles Deleuze’s transcendental empiricism. We will hold two hypotheses: firstly, that the main distinctive element of the latter in regard to the former is the absence of a condition of agreement between the fluxes of the different faculties; secondly, that the scene that Deleuze constructs in order to give an account of a disjunctive synthesis between heterogeneous elements is, in turn, inspired in Kant, more specifically in his Analytic of the sublime. Deleuze re-elaborates this scene, in his first philosophical system, in order to outline an encounter that savages sensibility and forces the different faculties to an autonomous exercise, which breaks with common sense and, nevertheless, still finds a harmony at the bottom of discordance.
Keywords: Deleuze; Kant; transcendental idealism; transcendental empiricism